A study of association between serum TSH levels and severity of heart failure in subclinical hypothyroidism - K., Sudha; S., Prabhu; J. Khan, Naazim; N. Teli, Ramesh (International Journal of Research in Medical Sciences, 2023)
Background: Cardiovascular diseases account for most common cause of death in India and world so far. One of the established risk factors for HF is subclinical hypothyroidism. Our study aimed to study the relationship between TSH levels in subclinical hypothyroidism and the clinical severity of HF in patients with pre-existing HF. Methods: This cross-sectional study was conducted in the hospitals attached to Bangalore medical college and research Institute. 51 patients with HF who had subclinical hypothyroidism who satisfied the inclusion criteria were included, Data was collected in the form of history, clinical examination and relevant investigations. Statistical analysis was performed using SPSS software, p<0.05 was considered significant. Results: Out of 51 patients, 70.6% were males and 29.4% were females and majority of the patients (33.3%) were aged 40 to 50 years. 35.3% patients had LV global hypokinesia, 31.4% had LV diastolic dysfunction and 21.6% had RWMA. Chi-square test showed statistically significant association between TSH and RWMA(p=0.00). Out of the 51 patients, NYHA Class-1 were 9.8%, Class-2 were 31.4%, Class-3 were 27.5% and Class-4 were 31.4%. Chi-square test showed no statistically significant association between TSH levels and NYHA class (p=0. 32). Conclusions: There was significant association between features suggestive of cardiac compromise on 2D-echocardiography with subclinical hypothyroidism, but there was no significant association between the severity of HF assessed clinically by NYHA class with subclinical hypothyroidism. Hence, our study couldn’t establish an association between severity of subclinical hypothyroidism on clinical severity of existing HF.